Aboriginaland big red diary, 1988 : land is life. ([Leichhardt, N.S.W.] : Pluto [Press Australia, 1987)
Includes sections on sovereignty, resistance, land, racism, the meaning behind the Aboriginal flag, the Aboriginal Tent Embassy, Pitjantjatjara victory, first mass strike of Aboriginal workers occurred in 1939, sacred women's site at Uluru, walk off at Wave Hill station, first industrial strike by Aboriginal people occurred in the Pilbara in 1946, in 1986-87 local Aboriginal people blocked a Northern Territory Government proposal to use their land as a site for a toxic chemical waste incinerator, extract from the Queensland Aborigines-Torres Straits Islanders Act 1972 stating no Aboriginal person shall leave a reserve without permission, 1982 Commonwealth Games demonstrations, in 1963 the Yirrkala people from Gove sent a petition painted on bark to the Commonwealth government, Gurindji Freedom Day 23 August, the Federated land Councils of Australia was formed at Noonkanbah in 1980, Aboriginal deaths in prison, Uluru handover in 1983, a directory of organisations, contact points and international support groups, quotes; images of posters.
Cover title.
Spine title: Big red diary, 1988.
Keywords: Diaries (Blank-books); Aboriginal Australians -- Land tenure; Aboriginal Australians -- Civil rights; Race relations - Racial discrimination; Politics and Government - Political action - Petitions - Yirrkala Bark Petition; Gurindji people (C20) (NT SE52-08); Politics and Government - National symbols and events - Bicentennial, 1988.; Settlement and contacts - Government settlements, reserves; Land rights; Politics and Government - Sovereignty; Pitjantjatjara people (C6) (NT SG52-11); Politics and Government - National symbols and events - Flag, Aboriginal; Politics and Government - Political action - Indigenous embassies and political missions - Tent Embassy, Parliament House, Canberra; Law enforcement - Custody - Deaths in custody; Sport - Commonwealth Games; Noonkanbah / Yungngora (WA West Kimberley SE51-12); Australia; Uluru / Ayers Rock (South Central NT SG52-08); Yirrkala (East Arnhem Land SD53-04); Northern Territory (NT); Nhulunbuy / Gove (East Arnhem Land NT SD53-04); Pilbara area (WA SF50, SF51, SG50); Daguragu / Kalkaringi / Wave Hill (Central NT SE52-08); Western Australia (WA)